EFEKTIVITAS PENAMBAHAN VITAMIN A DAN ZAT BESI PADA GARAM YODIUM TERHADAP STATUS GIZI DAN KONSENTRASI BELAJAR ANAK SEKOLAH DASAR - M. Saidin; Muherdiyantiningsih Muherdiyantiningsih; Endi Ridwan; Nur Ihsan; Astuti Lamid; Sukati Sukati; Lies Karyadi (Persagi, 2002)
THE EFFECT OF VITAMIN A AND IRON ADDED INTO IODIZED SALT ON NUTRITION STATUS AND LEARNING CONCENTRATION OF ELEMENTARY SCHOOL CHILDREN.Background: It was assumed that in some areas of Indonesia previously recognized as area of endemic goitre, thenutrition problem in that area became more complex due to crisis of economy. Probably some people in that area not only suffering from 100 but also vitamin A and iron deficiency. In this condition intervention of multinutrient is more reasonable than of single nutrient in improving nutrition status.Objectives: The aim of this study was to investigate the effect of vitamin A and iron added into iodized salt on iodine status and learning concentration of elementary school children in moderate endemic goiter area.Methods: The study design was